The Efficacy and Safety of Using a Stone Cone During Ureteroscopic Pneumatic Lithotripsy - kh.Mohammed, Waleed; S. AL-Azzawi, Issam; S. Khalaf, Yousif; Papatsoris, Athanasios (Diyala Journal of Medicine, 2025)
Background: Ureteroscopic fragmentation and extraction of ureteric stones is one of the most efficient minimal invasive treatment modalities. One of the drawbacks of this procedure, which occurs mainly during the fragmentation of upper ureteric stones, is the migration of proximal stones. Objectives: To study the efficacy and safety of the Stone cone in preventing proximal stone migration during ureteroscopic pneumatic lithotripsy. Patients and Methods: A retrospective data set of forty patients (25 male and 15 female), with symptomatic upper ureteral stones of greater than 7 mm in size, was collected from patients’ records. Patients were allocated into two equal groups: Group A (interventional group) underwent ureteroscopic pneumatic fragmentation using a stone cone, and Group B (control group) underwent ureteroscopic fragmentation without using a stone cone. The data on pre-operative patients, the stones dealt with, and the results of the procedure in both groups were all stated. Results: Pre-treatment patients and stone data (including patient age, gender, stone size, opacity, laterality, duration of symptoms, and degree of pelvicalyceal system dilatation) were comparable in both groups, with no statistically significant difference. The mean stone size was 12.7 mm in group A and 12.5 mm in group B. Stone migration occurred in 0 % in group A and 35% in group B (p=0.004), which led to a stone-free rate of 90% in group A and 60% in group B (p=0.028). Complications were minimal and comparable in both groups, and they were all amenable to conservative treatment. Conclusion: Use of a stone cone as a ureteric occlusive device was reasonably safe, helped prevent proximal stone migration, and led to statistically significant improvement in stone-free rate during pneumatic lithotripsy. Keywords: Ureteroscope, Renal Stone, Pneumatic Lithotripsy, Efficacy, Safety.